Influence of the Soil Structure Iteraction (ISE) on Surface Foundations and Cohesive Soils in the Structural Behavior of an Eight-Story Basement Building - Morales, Luis (2020)
Vibration periods and floor drifts are obtained from traditional models with a rigid base (perfect embedment), and others, where the floor is represented with impedance functions and, directly by finite non-linear elements (direct method). An eight-level building and a subsoil is used as the base project, which interacts with a soft non-cohesive soil. For the seismic loads were considered: the spectrum of the Ecuadorian Standard of Construction and the site, which corresponds according to the location of the project, to the one generated by the segment of the Quito fault called Puengasí. Additionally, time-scaled stories are used according to the site spectrum. The non-linear behavior of the structure is achieved by means of plastic ball joints. It is observed that the model that includes interaction through impedance functions varies up to 45% with respect to the rigid one, however, it gives conservative results with respect to the direct method.